Landuse Changes and Policy Directions for Agriculture due to Decreasing Agricultural Land in Mandalika Special Economic Zone - Zuhdiyah Matienatul Iemaaniah; Joko Priyono; Rika Andriati Sukma Dewi; Siska Ita Selvia (Universitas Pendidikan Indonesia, 2023)
Agricultural land is still priority for Indonesian people, the majority of whom are farmers. Along with the times and technological advances, as well as rapidly increasing population growth, agricultural land began to experience a widespread decline. The area of agricultural land that has decreased is a result of the construction of various public facilities that support an area. The Mandalika Special Economic Zone (SEZ) is experiencing land conversion from undeveloped land to built-up land due to the rapid development in the area. The purpose of this study is to determine changes in land use before and after the construction of the Mandalika Circuit and as a policy direction to increase agricultural land productivity. The research method uses GIS analysis for changes in land use and Focus Group Discussions (FGD) to obtain agricultural policy directions. The results obtained are that it is known that there has been a change in land use in Kuta Village after the Designation of the Mandalika Special Economic Zone with the Mandalika Circuit Development, and increasing the construction of built-up land. The landuse changes in ricefields decreased by 25.77 hectares, plantations 113.98 hectares, farms decreased by 86.06 hectares, while other lands is increase of 516.8 hectares. Directions for agricultural policy obtained directions that there has been a determination of sustainable agricultural land in Central Lombok Regency besides that there is a need for the implementation of Sustainable Food Homes (RPL), the concept of agrosilvopastura agriculture, waste utilization and the need for the development of agriculture-based tourism.